Mucinous cystic neoplasm of the pancreas with severe dysplasia during pregnancy: Case report and review of the literature - Hiroyuki Tsuda; Tomomi Kotani; Seiji Sumigama; Yukio Mano; Yoshie Shimoyama; Fumitaka Kikkawa (Elsevier, 2012)
Objective: Mucinous cystic neoplasm (MCN) of the pancreas occurs mainly in women aged 40-60 years, so it is extremely rare in pregnant woman. Case Report: A 28-year-old woman in the ninth week of pregnancy was referred to our hospital due to a tumor of the abdominal cavity. Abdominal ultrasound demonstrated a huge multicystic lesion in the left upper abdomen. There are mural nodules and hypertrophic septa partially with the presence of blood flow inside the tumor. Endoscopic ultrasonography was performed and a diagnosis of possible pancreatic MCN was made. At the second trimester, distal pancreatectomy with splenectomy was performed. Histopathological analysis of the specimen revealed a pancreatic MCN with severe dysplasia. Immunohistochemically, the tumor was positive for both progesterone and estrogen receptors in the stromal cell nuclei; moreover, MIB-1 stained positive in 10-20% of the nuclei in the epithelium with severe dysplasia. Conclusion: MCN carries malignant potential, therefore, early detection and complete surgery is recommended. MCN in pregnancy is rare and the abdomen is distended during pregnancy, so clinicians can easily miss the presence of the tumor. We should recognize the presence of MCN in pregnant woman. We speculate that the presence of blood flow within the tumor and MIB-1-positive cells can be a predictor for premalignant or malignant MCN.